Studi Etnobotani Mangrove pada Masyarakat Pesisir Muara Gembong, Bekasi, Jawa Barat - R. Indarjani; Aryono Wibowo (Journal of Tropical Ethnobiology, 2021)
Realised the impacts of ecotourism to the local community, the study of ethnobotany mangrove was conducted to elaborate perception of local coastal communities related to mangrove habitat around them. Descriptive research method was applied. Interview technique was employed using systematic and structured instrument and depth interviewed was followed to the selected respondents. The instrument of questionare was validated before field survey took place. However, due to Covid 19 pandemic situation, the questionare then was distributed via online. From 100 expected respondents, only 55 questionerres were returned. The result showed that all local people (100%) was familiar with mangrove and 65% (36 respondent) had adequate knowledge about mangrove and its benefits such as for medicine (14%), for food (33%), for house hold (15%), craft (15%) and other purposes (23%). In regard to the connection of mangroves with industries, the data showed that 23% respondents answered positive and 77% was divided between no and have no idea. The research also identified consent of local community to ecotorurims program and found 94% approved and support the program, even though only four respondents (6%) has joint in tourism training that conducted by government. For the future of mangrove in Muara Gembong as ecotourism, the expectancy of community was relatively various, included financial assistance (35%), ecotourism trainings (7%), education (10%), mangrove cultivation and management (21%), and others was 17%.